The Spiritual Role of Lake Across Legends in Indonesia: Nature as (More Than) the Divine Retributor - Madilah, Aryl Timothy (Proceedings of English Linguistics and Literature, 2024)
Across many legends in Indonesia, nature takes the role of the divine retribution, the ultimate punishment against evil and wrongdoings. This depiction of nature may at first glance seem negligible; however, this depiction may also be seen as describing the relationship that spiritual ecology holds between human and nature. This paper compares the role of the lake-creation in four written legends across Indonesia: the Legend of Danau Toba from North Sumatra, the Legend of Rawa Pening from Central Java, the Legend of Danau Tondano from North Sulawesi, and the Legend of Danau Kelimutu from East Nusa Tenggara. In these legends, the apparent role of divine retribution nature has over the character highlights humans as a part of nature, and not as its master. It reflects how the people owning these legends see themselves in relation to the environment where they live, a view that is certainly applicable to modern life. The view that nature executes divine retribution towards human’s malevolence serves as a reminder that nature will always be the bigger picture of human life despite its seemingly confined place in a man-centered society